Barriga Verde Popular Puppets Theatre: the Impossible Patrimonialization - Campoi García, Comba (Madrygal. Revista de Estudios Gallegos, 2020)
Grassroots movements that claim that the culture of popular classes has to be included in the intangible cultural heritage label, do so with the positive intention of preserving and legitimizing those forms of culture. By doing so, they intend to give value to creative processes that were traditionally undervalued by the Academy. An example of this is Barriga Verde, a traditional puppet show that enjoyed great popularity in Galicia until 1964. Its eminently subversive character, in line with the European tradition from which it comes, makes it an unattractive cultural asset for those who understands heritage as a way to generate economic benefits regardless of the original meaning of the assets exploited. The Cultural Association “Morreu o Demo” is working precisely to revive the show without having to enclose it into heritage category.